Impact and cost-effectiveness of potential interventions against infant respiratory syncytial virus (RSV) in 131 low-income and middle-income countries using a static cohort model. Issue 4 (24th April 2021) - Baral, Ranju; Higgins, Deborah; Regan, Katie; Pecenka, Clint
Abstract : Objectives: Interventions to prevent childhood respiratory syncytial virus (RSV) disease are limited and costly. New interventions are in advanced stages of development and could be available soon. This study aims to evaluate the potential impact and cost-effectiveness of two interventions to prevent childhood RSV—a maternal vaccine and a monoclonal antibody (mAb). Design: Using a static population-based cohort model, we evaluate impact and cost-effectiveness of RSV interventions, from a health systems perspective. The assumed baseline efficacy and duration of protection were higher for the mAb (60%–70% efficacy, protection 6 months) compared with the maternal vaccine (40%–60% efficacy, protection 3 months). Both interventions were evaluated at US3 and US5 per dose for Gavi and non-Gavi countries, respectively. A range of input values were considered to explore uncertainty. Settings: 131 low-income and middle-income countries. Participants: Pregnant women and live birth cohorts. Interventions: Maternal vaccine given to pregnant women and mAb given to young infants. Primary and secondary outcome measures: Disability-adjusted life years averted, severe case averted, deaths averted, incremental cost effectiveness ratios. Results: Under baseline assumptions, maternal vaccine and mAbs were projected to avert 25% and 55% of RSV-related deaths among infants younger than 6 months of age, respectively. The average incremental cost-effectiveness ratio per disability-adjusted life year averted was US1342 (range US800–US1866) for maternal RSV vaccine and US431 (range US167–US692) for mAbs. At a 50% gross domestic product per capita threshold, maternal vaccine and mAbs were cost-effective in 60 and 118 countries, respectively. Conclusions: Both interventions are projected to be impactful and cost-effective in many countries, a finding that would be enhanced if country-specific Gavi cofinancing to eligible countries were included. mAbs, with assumed higher efficacy and duration of protection, are expected to be more cost-effective than RSV maternal vaccines at similar prices. Final product characteristics will influence this finding.